MOTUs: Profiling Taxonomic Composition, Transcriptional Activity and Strain Populations of Microbial Communities. Issue 8 (13th August 2021) - Ruscheweyh, Hans‐Joachim; Milanese, Alessio; Paoli, Lucas; Sintsova, Anna; Mende, Daniel R.; Zeller, Georg; Sunagawa, Shinichi
Abstract: The mOTU profiler, or mOTUs for short, is a software tool that enables the profiling of microbial communities in terms of their taxonomic composition, relative abundance of metabolically active members, and diversity of strain populations. To this end, it maintains a database of single‐copy phylogenetic marker gene sequences, which are used as a reference to which short read metagenomic and metatranscriptomic reads are mapped for the identification and quantification of microbial taxa. Here, we describe the most common use cases of the mOTU profiler in two basic protocols. Additional supporting protocols provide information on its installation and in‐depth guidance on adjusting its settings for increasing or decreasing the stringency with which taxa are detected and quantified, as well as for customizing the output file format. Guidelines for understanding the profiling results are provided, along with additional information on unique features, methodological details, and the development history of the tool. © 2021 The Authors. Current Protocols published by Wiley Periodicals LLC. [Correction added on May 17, 2022, after first online publication: CSAL funding statement has been added.] Basic Protocol 1 : Metagenomic and metatranscriptomic mOTU profiling Basic Protocol 2 : Metagenomic SNV profiling Support Protocol 1 : Installing mOTUs Support Protocol 2 : Profiling pipeline–step by step Support Protocol 3 : The mOTUs profiling routine using advanced parameters Support Protocol 4 : Metagenomic SNV calling: advanced parameters